The biblical age of judges without the letter ‘g’: translation of Book VII of the lipogram De aetatibus mundi et hominis by Fulgentius the Mythographer - Santos Júnior, Cristóvão José dos (Revista Archai, 2020)
This work consists of the first lipogrammatic translation and the first ever made into the Portuguese language of Book VII of the work De aetatibus mundi et hominis, credited to the late and African writer Fulgentius, the Mytographer (late 5thÂ ”“ early 6th century). De aetatibus is a consecutive lipogram that has a prologue and other 14 Books, with constriction in the initial 14 letters of Fulgentius’ alphabet. In this seventh section of the work, Fulgentius discusses the biblical age of the judges, avoiding the use of lexical units containing the letter ’g’, which was cultivated in the proposed translation text, which was developed from the critical edition by Rudolf Helm (1898).